Asymptotic normality of a discrete procedure of stochastic approximation in a semi-Markov medium - Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain sufficient conditions for the asymptotic normality of a jump procedure of stochastic approximation in a semi-Markov medium using a compensating operator of an extended Markov renewal process. The asymptotic representation of the compensating operator guarantees the construction of the generator of a limit diffusion process of the Ornstein-Uhlenbeck type.